2017
DOI: 10.1093/mnras/stx1321
|View full text |Cite
|
Sign up to set email alerts
|

Stark broadening of Zr iv spectral lines in the atmospheres of chemically peculiar stars

Abstract: Stark widths for 18 Zr Iv spectral lines have been calculated by using the modified semiempirical method. The obtained results have been used to investigate the influence of Stark broadening on the spectra of atmospheres of chemically peculiar stars of A spectral type and hydrogen-rich DA and helium-rich DB white dwarfs. Our results have been used also to test possibility to predict new data using some approximate methods developed on the basis on regularities and systematic trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In Tables 1 and 2, calculated Stark widths of 18 Zr IV lines made by different estimation methods mentioned above are compared to previous MSE calculations of Stark FWHM Majlinger et al [5]. All results presented in Tables 1 and 2 are calculated for a temperature of 10,000 K and electron density of 10 23 m −3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Tables 1 and 2, calculated Stark widths of 18 Zr IV lines made by different estimation methods mentioned above are compared to previous MSE calculations of Stark FWHM Majlinger et al [5]. All results presented in Tables 1 and 2 are calculated for a temperature of 10,000 K and electron density of 10 23 m −3 .…”
Section: Resultsmentioning
confidence: 99%
“…First we will estimate Stark widths with the simple formula of Cowley [7] which is often in use by some modern authors in original or modified form (see, for example, Killian et al [11], Ziegler et al [12] and Przybilla et al [13]) and which has recently used by our team for comparison with MSE calculated values of Stark widths of Lu III spectral lines too, see Majlinger et al [14]. In Majlinger et al [5] we derived it from the Griem [10] semiempirical formula at low temperature limit and added the contribution to the width of the lower energy level. In such a case, the difference between original formula of Cowley and the modified formula in [5] is for a factor 2/3 3/2 plus the contribution of the lower energy level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromium in various ionization stages from Cr I to Cr VI has been observed and in the spectra of white dwarfs, where the Stark broadening is often the dominant broadening mechanism in wide layers of the atmosphere [19][20][21][22][23][24][25][26][27]. For example, Cr I has been found by Gianninas et al [28] in an extremely low mass white dwarf in the SDSS J074511.56+194926.5 binary system and by Dufour et al [29] in the spectrum of DZ white dwarf G165-7; Cr II spectral lines were identified by Klein et al [30] in the spectrum of white dwarf GD 40, observed on the Keck I telescope at Mauna Kea Observatory; and, for example, Cr V and Cr VI by Rauch et al [31] in the spectrum of the white dwarf central star of Sh 2-216.…”
Section: Introductionmentioning
confidence: 99%